Heat Transfer Analysis in 4-Pass 500HP Fire-Tube Boiler - Rahmani, Ahmed; Djeddou, Messaoud (New Approaches in Engineering Research Vol. 10, 2021)
This paper deals with a steady-state heat transfer analysis in a 4-pass fire-tube boiler. A computational program has been developed to study the heat transfer between the combustion gases and the boiler tube walls. On these surfaces, the energy balance was established, taking into account the heat transfer by convection and thermal radiation. The heat transfer characteristics, namely, the heat flux densities and the corresponding wall temperatures, are evaluated for different operating conditions. The modeling approach was validated by comparing the calculated outlet gas temperature against the experimental data, of the PFTA 500HP fire-tube boiler, for three types of fuels and various operating pressures. The comparison shows that the calculation results are in good agreement with the boiler's experimental data. A parametric analysis has also been conducted to investigate the working pressure effect on the boiler thermal behavior.